Disaster operations and decision making - Huder, Roger C. (Hoboken, N.J. : John Wiley & Sons, 2012)
'This book focuses on crisis decision making and the creation of the systems and procedures needed to carry out those decisions. Based on years of research, experience in the civilian emergency management sector, and the adaptation of specific military procedures to civilian needs, it assists the reader in honing decision making, team building, and operational skills and knowledge to respond to natural and manmade disasters. With information on current technology and lessons learned, the book also emphasizes the integration of state-of-the-art crisis decision making procedures and emergency disaster operations'--
Includes bibliographical references and index.
Keywords: Emergency management; Crisis management; Decision making; TECHNOLOGY & ENGINEERING / Industrial Health & Safety